Exploring trainees' learning experiences with an Initial Teacher Education award (Lifelong Learning Sector) at one Higher Education institution in the UK - Machin, Lynnette (2013)
This study was borne out of a necessity to discover the best approach to deliver a Diploma in Teaching in the Lifelong Learning Sector (DTLLS) award that would meet the needs of trainee teachers and at the same time meet the demands of political and organisational agendas. The aim of the study was therefore to explore, identify and to gain an increased understanding of the factors that influenced the learning experiences of a group of trainee teachers working in the lifelong learning sector who were enrolled onto a DTLLS award. This award was accredited by a medium sized university located within an urban, high unemployment, Government regeneration area, in the Midlands (UK). It was delivered at five of the university's partnership colleges where trainees were required to attend formal classroom-based training sessions for four hours each week. An interpretative, case study, multi-method approach was used to gather data from 327 trainees, twelve of whom volunteered to be interviewed. Other data was gathered from interviews with eleven teacher educators, questionnaires distributed to all 327 trainees, data drawn from the university's Information Service Department (I.S.) and from the journal entries that I kept during the time of the research. Four themes emerge from the data gathered; diversity, identity, conditions for learning and learner autonomy. It is the interpretation and illumination of the complexity, as well as the plurality, of relationships that exist within and across these themes, that adds to, as well as supports, the field of literature that is already available. The evidence presented within these four themes relates to the variations in trainees' characteristics and backgrounds, support available for the trainees and an over-burdensome, regulated initial teacher education model. Based upon the analysis of the findings, this study suggests that initial teacher education within the Lifelong Learning Sector (LLS) should be modelled around a supportive framework that encourages trainees' professional enquiry and building of own contextualised content. Additionally, (further) acknowledgement of trainees' strong sense of different identities and diversities is required as is an increased focus on processes that support the development of trainees' learning capacities. This thesis contends that doing this would support trainees' growth in becoming more self-organised, autonomous and reflective practitioners - able to take control of their own learning within whatever initial teacher education model is in current existence.